2012
DOI: 10.1037/a0027016
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration in the presence of an electronic health record.

Abstract: Recent laws in the United States incent healthcare practices to adopt electronic health records (EHRs). While there is extensive research related to EHRs generally, there is a dearth of EHR research specific to collaborative care settings. This study reports responses from 101 collaborative care offices who completed a 13-question online survey. The mixed-methods analysis provides insights as to the satisfaction, obstacles, and solutions to interdisciplinary collaboration in the presence of an EHR. Respondents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 7 publications
(8 reference statements)
0
26
0
Order By: Relevance
“… 9 , 18 , 20 , 24 , 25 EHRs were the most common health information technology used. 12 , 18 , 19 , 21 23 , 26 , 29 , 30 A single study used the Aging Brain Care Medical Home model to facilitate care coordination. 18 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… 9 , 18 , 20 , 24 , 25 EHRs were the most common health information technology used. 12 , 18 , 19 , 21 23 , 26 , 29 , 30 A single study used the Aging Brain Care Medical Home model to facilitate care coordination. 18 …”
Section: Resultsmentioning
confidence: 99%
“…EHRs were the most commonly assessed technology for care coordination (n=9).12,18,19,21–23,26,29,30 In a survey of 101 collaborative care offices, 95% of primary care physicians and 87% of mental health clinicians used EHRs. 23 Across three studies, the identified advantages of using EHRs included increased shared access of patient information between providers; 22 high satisfaction with billing, scheduling, and screening for mental health; 23 and utility in promoting human rights for patients with mental illness in the correctional system. 29 A single study showed the utility of touch screen technology with wireless tablet computers for mental health screening.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A huge challenge must be overcome considering the regional differences and the telehealth implementation already experienced in Brazil's public health. Mainly, regarding resistance of technology implementation in the work environment, higher number of cases and with greater complexity to be followed, as well as confidentiality and health record usability by multidisciplinary teams 15,[29][30][31] . Historically, now there is an opportunity to articulate a TMH national program and coordinated research to detect high-risk status, early stage disorder, combine pharmacological and psychosocial interventions in a stepped-care fashion with long-term follow-up based on scientific evidences looking forward to improve mental health care service delivery and access to proper mental health care in primary care.…”
Section: Discussionmentioning
confidence: 99%